The Role of Video in the Flipped Language Classroom - Angelika Verch; Elke Nissen (The Canadian Network for Innovation in Education (CNIE), 2021)
Flipped classrooms have become a widespread form of teaching. Yet, there is no consensus on how to define flipped (language) learning. Several authors consider the use of videos that prepares in-class activities as an essential principle. The article presents a study which examined the actual roles of videos in a corpus of 52 descriptions by L2 teachers of flipped language class settings and using Willis' 1983 framework. In the corpus videos played a central role in before-class activities; a large number of videos were used. The roles that videos played in before-class activities in the settings did not all correspond to Willis' framework; those which did not fit corresponded to direct instruction. The definition of a flipped setting was found to be unclear, as in a quarter of the descriptions the criteria did not apply. Video was not found to be necessarily constitutive for flipped language classes.